Prognostic Factors Affecting Mortality Among Patients Admitted to the Intensive Care Unit with Acute Hypoxemic Respiratory Failure - Kerem Ensarioğlu; Melek Doğancı; Mustafa Özgür Cırık; Mesher Ensarioğlu; Erbil Tüksal; Münire Babayiğit; Seray Hazer (Diagnostics)
Background/Objectives: Acute hypoxemic respiratory failure is a significant condition commonly seen in intensive care units (ICUs), yet specific prognostic markers related to it for mortality remain largely unstudied. This study aimed to identify parameters that influence mortality in ICU patients diagnosed with type 1 respiratory failure. Methods: A retrospective cohort study was conducted at a tertiary care hospital, including patients admitted to the ICU between March 2016 and March 2020. The study included patients with type 1 respiratory failure, while exclusion criteria were prior long-term respiratory support, type 2 respiratory failure, and early mortality (<24 h). Data on demographics, comorbidities, support requirements, laboratory values, and ICU scoring systems (APACHE II, SOFA, SAPS II, NUTRIC) were collected. Binomial regression analysis was used to determine independent predictors of 30-day mortality. Results: Out of 657 patients screened, 253 met the inclusion criteria (mean age 70.6 ± 15.6 years; 65.6% male). Non-survivors (n = 131) had significantly higher CCI scores; greater vasopressor requirements; and elevated SAPS II, APACHE, SOFA, and NUTRIC scores. Laboratory findings indicated higher inflammatory markers and lower nutritional markers (albumin and prealbumin, respectively) among non-survivors. In the regression model, SAPS II (OR: 13.38, p = 0.003), the need for inotropic support (OR: 1.11, p = 0.048), NUTRIC score (OR: 2.75, p = 0.014), and serum albumin (inverse; OR: 1.52, p = 0.001) were independently associated with mortality. The model had an AUC of 0.926 and classified 83.2% of cases correctly. When combined, SAPS II and mNUTRIC had more AUC compared to either standalone scoring. Conclusions: SAPS II, vasopressor requirements, mNUTRIC score, and low serum albumin are independent predictors of 30-day mortality in patients with acute hypoxemic respiratory failure. These findings support the integration of nutritional assessment, a combination of available scoring systems and comprehensive scoring into routine ICU evaluations for this patient group.